Melatonin versus gabapentin as premedication for anxiolysis and attenuation of hemodynamic response to laryngoscopy and intubation in general anesthesia - Kalpana Rajendra Kulkarni,; Pradhan Monnaiah K,; Padma S,; Hema Viswanath K, (Asian Journal of Medical Sciences, 2024)
Background: Perioperative anxiety adversely affects mental and physical well-being and it is associated with increased pain, stressor responses with general anesthesia (GA), and nausea-vomiting leading to delayed recovery. Recent studies have proven melatonin and gabapentin provide sedation, anxiolysis, and reduced pressure responses. Aims and Objectives: This study aimed to compare melatonin and gabapentin as premedication for anxiolysis and attenuation of hemodynamic response to GA. Post-operative pain and sedation were also compared. Materials and Methods: A total of 99 subjects (n=33 in each group) between 18 and 60 year of age, ASA I/II scheduled for elective abdominal surgeries of < 3h under GA were included in the study. Patients in Group A were administered melatonin (10 mg×2 tab.), those in Group B were administered gabapentin (400 mg×2 tabs), and those in control Group C were treated with Vitamin C (500 mg×2) before 2 h of surgery. At 0 min, 30 min, and 60 min assessments of anxiety, sedation, cognition, psychomotor function, and orientation were done. Results: There were significantly low anxiety scores in Groups M and G compared to Group C at 60 min and 90 min (P=0.0000). Sedation score was significantly less in Group C patients compared to Group M and G at 30 min (P=0.0008), 60 min, and 90 min (P=0.0000) intervals. Heart rate and mean arterial pressure were increased in Group C patients as compared to Groups M and G. Conclusion: This study showed that melatonin had more anxiolytic and less sedative action, so also cognitive functions and orientation were well preserved in melatonin-treated subjects than in gabapentin. Hemodynamic responses were comparable in melatonin- and gabapentin-treated patients.